2004
DOI: 10.1094/mpmi.2004.17.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Reactive Oxygen Species Do Not Elicit Hypersensitive Cell Death but Induce Apoptosis in the Adjacent Cells During the Defense Response of Oat

Abstract: Nitric oxide (NO) acts as a signaling molecule in many cellular responses in plants and animals. Oat plants (Avena sativa L.) evoke the hypersensitive response (HR), which shares morphological and biochemical features with mammalian apoptosis, such as DNA laddering and heterochromatin condensation, in response to the avirulent crown rust fungus (Puccinia coronata f. sp. avenae). We examined the role of NO and reactive oxygen species (ROS) in the initiation of hypersensitive cell death, which is induced by dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 52 publications
4
73
2
2
Order By: Relevance
“…They consist in non-fluorescent molecules that become fluorescent when oxidised by ROS, and the emitted fluorescence can be observed by fluorimetry and/or by fluorescent microscopy, an advantage of such probes (Benikhlef et al, 2013;Bulgakov et al, 2012;Fester and Hause, 2005;Guo et al, 2010;Kolla et al, 2007;L'Haridon et al, 2011;Li et al, 2007;Liu et al, 2010;Ma et al, 2013;Peleg-Grossman et al, 2012;Plancot et al, 2013;Tada et al, 2004;Wen et al, 2008;Ye et al, 2013). Luminol or luminol analogues are sensitive chemiluminescent probes used to quantify a relative intensity of ROS by counting the emitted light with a luminometer, CDD camera or a scintillation counter (Dubreuil-Maurizi et al, 2010;Flury et al, 2013;Kunz et al, 2006;L'Haridon et al, 2011;Mersmann et al, 2010).…”
Section: Detection Of Rosmentioning
confidence: 99%
“…They consist in non-fluorescent molecules that become fluorescent when oxidised by ROS, and the emitted fluorescence can be observed by fluorimetry and/or by fluorescent microscopy, an advantage of such probes (Benikhlef et al, 2013;Bulgakov et al, 2012;Fester and Hause, 2005;Guo et al, 2010;Kolla et al, 2007;L'Haridon et al, 2011;Li et al, 2007;Liu et al, 2010;Ma et al, 2013;Peleg-Grossman et al, 2012;Plancot et al, 2013;Tada et al, 2004;Wen et al, 2008;Ye et al, 2013). Luminol or luminol analogues are sensitive chemiluminescent probes used to quantify a relative intensity of ROS by counting the emitted light with a luminometer, CDD camera or a scintillation counter (Dubreuil-Maurizi et al, 2010;Flury et al, 2013;Kunz et al, 2006;L'Haridon et al, 2011;Mersmann et al, 2010).…”
Section: Detection Of Rosmentioning
confidence: 99%
“…ROS in association with salicylic acid are proposed to mediate the establishment of systemic defenses (Durrant and Dong 2004). The cytological studies have revealed that ROS and NO are associated with cell death adjacent to infected cells and so that both signals modulate each other's accumulation (Tada et al 2004). Upregulation of NADPH oxidases was reported in the resistant banana cultivar in response to Foc (TR4) infection (Li et al 2012).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…The key role of NO as a signal molecule and in defence processes of plants was documented in the relationships of plants to wound reaction (Orozco-Cardenas and Ryan 2002) and interactions with viruses, bacteria, oomycetes (e.g. Sedlářová et al 2011) and fungi (Tada et al 2004;Prats et al 2005;Piterková et al 2009). NO is vital for initiation and development of a hypersensitive response in plants, modification of gene expression and synthesis of PR (pathogenesis related) proteins (Wendehenne et al 2004;Zeier et al 2004;Mur et al 2006;Zaninotto et al 2006).…”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%